RANCANG BANGUN SISTEM INFORMASI KESISWAAN BERBASIS WEBSITE MENGGUNAKAN METODE EXTREME PROGRAMMING (STUDI KASUS: SMA SEJAHTERA 1 DEPOK) - Dina Aulia, (2023)
SMA Sejahtera 1 Depok in the management of each data uses Microsoft Excel and has not been carried out optimally because there is no database integrated and not structural it can be at risk with the accuracy, precision of searching, and redundancy of data. The person in charge of the data is held by the Deputy Head of Student Affairs where this is not aligned with the duties and responsibilities of the management structure at SMA Sejahtera 1 Depok. Evaluation of each data has not been optimal which causes it difficult for schools to evaluate data every year. The researcher's goal's to develop a Website-based Student Information System at SMA Sejahtera 1 Depok. The benefit of this research is to provide convenience for stakeholders in managing and obtaining information on student data at SMA Sejahtera 1 Depok. The method used in this research is Extreme Programming method. The results of this study are in the form of a website-based Student Information System that can manage any data held by the Deputy Head of Student Affairs handle witby admin who can manage Academic Year Data, Department Data, Class Data, Student Biodata, Student Achievements, Notes Students, and Student Mutation Data which can facilitate SMA Sejahtera 1 Depok in managing more effectively, efficiently, integrated into databases, accuracy, and reducing data redundancies.